Systematic review and network meta-analysis of outcomes of transcatheter strategies and surgical shunts for treatment of duct-dependent cyanotic congenital heart disease - Chee, Qiao Zhi; Buvaneswarran, Santosi; Chen, Ching Kit; Shen, Liang; Quek, Swee Chye (Frontiers in Cardiovascular Medicine, 2025)
IntroductionCyanotic congenital heart disease with duct-dependent pulmonary blood flow requires initial palliation before definitive repair. Traditionally, these were surgical systemic-to-pulmonary shunts (SPS) such as the modified Blalock-Taussig-Thomas shunt. Transcatheter procedures are recently emerging as alternative options. Previous reviews have compared ductal stenting (DS) or right ventricular outflow tract (RVOT) intervention to surgical SPS, but none compared all three strategies in a single meta-analysis.MethodsWe performed a systematic review and network meta-analysis for a three-way comparison of DS, RVOT intervention, and surgical SPS as initial palliation in children aged 0–3 with cyanotic congenital heart disease. Primary outcomes were mortality rates, complication rates, and re-intervention rates. MEDLINE, EMBASE, and Cochrane databases were searched for publications from 2003 to 2023. References of previous systematic reviews were screened.ResultsTwenty publications were included for analysis, for a total of 4,441 patients. Transcatheter options consistently ranked superior to surgical SPS for Early and Overall Mortality. DS also outperformed surgical SPS for Procedural Complications. Surgical SPS was worst for Early Re-interventions, but outperforms both transcatheter options for Overall Re-interventions and Intra-procedural Mortality. Both DS and RVOT stenting conferred a shorter overall hospitalization duration compared to surgical SPS, and DS also gave a shorter length of stay in intensive care compared to surgical SPS.ConclusionsTranscatheter options are viable, safe, and attractive alternatives to traditional surgical shunts in the treatment of duct-dependent cyanotic heart disease. With wider adoption, increased collective expertise will help to further improve patient outcomes of these less-invasive techniques.Systematic Review RegistrationPROSPERO (CRD42024489748).